Tomb and temple - Griffith-Jones, Robin,Fernie, Eric (The Boydell Press, 2018)
Jerusalem - earthly and heavenly, past, present and future - has always informed the Christian imagination: it is the intersection of the divine and human worlds, of time and eternity. Since the fourth century, it has been the site of the round Church of the Holy Sepulchre, built over the empty tomb acknowledged by Constantine as the tomb of Christ. Nearly four hundred years later, the Sepulchre's rotunda was rivalled by the octagon of the Dome of the Rock. The city itself and these two glorious buildings within it remain, to this day, the focus of pilgrimage and of intense devotion.Jerusalem and its numinous buildings have been distinctively re-imagined and re-presented in the design, topography, decoration and dedications of some very striking and beautiful churches and cities in Western Europe, Russia, the Caucasus and Ethiopia. Some are famous, others are in the West almost unknown. The essays In this richly illustrated book combine to do justice to these evocative buildings' architecture, roles and history. The volume begins with an introduction to the Sepulchre itself, from its construction under Constantine to the Crusaders' rebuilding which survives to this day. Chapters follow on the Dome of the Rock and on the later depiction and signifcance of the Jewish Temple. The essays then move further afeld, uncovering the links between Jerusalem and Byzantium, the Caucasus, Russia and Ethiopia. Northern Europe comes fnally into focus, with chapters on Charlemagne's chapel at Aachen, the role of the military orders in spreading the form of the Sepulchre, a gazetteer of English rounds, and studies of London's New Temple.
Keywords: Architektur; Heiliges Grab; Rezeption; Orthodoxe Kirche; Kirchenbau; Zentralbau; Rundbau; Church architecture; Symbolism in architecture